2014
DOI: 10.31018/jans.v6i1.372
|View full text |Cite
|
Sign up to set email alerts
|

A study on dog bite incidence in Union Territory of Dadra & Nagar Haveli, India

Abstract: Abstract:The injuries caused by dog bites have grown to such epidemic proportions that they are now considered a major public health concern. The epidemiology of dog bites in the UT of Dadra & Nagar Haveli has been evaluated, for the year 2012. This assessment included victims age, sex, biting site and season of the year. During the study, a total of 938 dog bites, were reported from aforesaid place. Of all the dog bites reported, 39.6% victim belonged to age group upto 0-15 year (children) and 60.4% were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…Patients between the age group of 0-15 years were the maximum dog bite victims and as per the age and sex distribution males were more bitten than females (Table 1). Similar results were seen in the study done by Khan et al Jain et al 6,7 Wound care is important, local cleaning of wound after animal bite reduces risk by 80%. In the indepth interview it is found that 43.07% of the patients had washed the wound immediately.…”
Section: Discussionsupporting
confidence: 88%
“…Patients between the age group of 0-15 years were the maximum dog bite victims and as per the age and sex distribution males were more bitten than females (Table 1). Similar results were seen in the study done by Khan et al Jain et al 6,7 Wound care is important, local cleaning of wound after animal bite reduces risk by 80%. In the indepth interview it is found that 43.07% of the patients had washed the wound immediately.…”
Section: Discussionsupporting
confidence: 88%
“…The commonest age group reported by some of the series for dog bites is between 1-15 years. 9 Dog bites typically affects children more commonly than adult. 10 Our study did have similar report.…”
Section: Discussionmentioning
confidence: 99%
“…1). Out of these 35 included studies, 25 reported epidemiological outcomes only: 19 cross-sectional studies, 4,20-39 3 cohort studies (2 prospective cohort 40,41 and 1 retrospective cohort studies 42 ) and 1 modeling study. 43 Nine studies reported economic outcomes only [44][45][46][47][48][49][50][51][52] and all of these studies were partial economic evaluation (2 prospective cohort studies, 51,52 6 cross-sectional studies [44][45][46][48][49][50] and 1 on implementation cost of interventions 47 ).…”
Section: Search and Screeningmentioning
confidence: 99%
“…Only one modeling study reported all the three outcomes: epidemiological, economic and humanistic. 1 Out of 35 included studies, 23 were hospital (or clinic) based, [20][21][22][24][25][26][27][28][29][30][31]38,41,42,[44][45][46][47][48][49][50][51][52] 9 were community (or household) based 4,23,[32][33][34][35]37,39,40 and 2 were modeling studies at country level 1,43 and was laboratory-based study. 36…”
Section: Search and Screeningmentioning
confidence: 99%
See 1 more Smart Citation